A SEMIOTIC ANALYSIS ON ELDORADO POEM BY EDGAR ALLAN POEM - Pungky Farras; Ely Nurmaily (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2020)
The research is entitled “A Semiotic Analysis on Eldorado poem by Edgar Allan Poe”. This study is aimed to know the meaning of the symbols of Gallant knight, Eldorado, shadow, a pilgrim shadow, shade, over the mountains related to the socio-historical issue. This study is also used in the qualitative method and library research. Starting from the writers’ interest in the poem and think that, the poem has a unique word inside it. In this research, the knight who do the long journey to search for “Eldorado”. This study focuses on semiotic analysis, which uses the semiotic approach. Charles Sanders Pierce is the theory that the writers use to analyze “Eldorado” poem by Edgar Allan Poe. The use of semiotic analysis is to find a symbol of Eldorado poem. This study also used the socio-historical approach that correlates with the Eldorado poem.The symbols of Eldorado poem, a gallant knight, Eldorado, shadow, a pilgrim shadow, shade, and over the mountains represent the meaning, where Eldorado is true of a wealthy city made of gold. However, Eldorado is not a place but a person. The whole journey of Europeans to find a golden city is in vain. Eldorado's poem is related to the symbol of time in 1849 in California, where the attitude of the Muisca tribe is different from the people of Europe who see gold as a symbol of wealth, as well as power. Furthermore, the minds of Europeans who heard the story were only fascinated by how much gold was thrown into the lake or buried in shrines throughout Colombia. Not the meaning of gold itself. That is why Poe revealed a poem entitled Eldorado which means that Eldorado itself was a rich king who had covered his entire body with gold.